Typology Of Communicative Strategies In Cognitive And Pragmatic Analysis - Najmiddinova Sarafroz Najmiddin qizi (International Journal Of Literature And Languages, 2026)
The purpose of this article is to study the classification of communicative strategies from the prism of cognitive and pragmatic approaches. In this study, the communicative strategies are defined as elements of speech behavior that are purposeful, created and executed in a speech act in order to achieve a pre-defined communicative outcome. Based on the theories of cognitive science, pragmatics, and the theories of discourse that the author discusses, the article attempts to establish a systematic classification of communicative strategies and analyze their roles in discourse construction.